HM and EHM as discourse markers in German WhatsApp chats. (March 2021) - König, Katharina
Highlights:  and  have discourse-pragmatic functions. In responsive postings they indicate that finding the answer required some thought. They usually do not halt the emerging chat but relate the posting to previous discourse.  -postings align with the current course of action and take a cooperative stance.  can also be used to disalign and express a stance of irritation. Abstract: The paper studies the discourse-pragmatic functions of hesitation markers such as  and  in a corpus of text-based German WhatsApp dialogues. The sequential analysis of these markers suggests that they are used by texters to indicate different discourse relations and stances. Responsive  (i.e. markers without a vowel) usually indexes alignment with the current course of action; it frames the following contribution as the preliminary result of a longer thought process, and often invites other users to deliberate the matter at hand.  (markers with a vowel), in contrast, can also index processing which takes issue with a preceding posting and hence disaligns with the projected course of action. In opposition to recent studies highlighting the conversational nature of WhatsApp dialogues, the analysis shows that texters make use of different levels of incrementality. Prototypically, texters do not deploy  and  as stand-alone elements of a posting to indicate that they are still deliberating and need more time to produce their next contribution. Rather, they use them as initial framing devices in longer postings actively suspending an incremental exchange of messages. It is argued that these instances should not be classified as hesitation markers, fillers or planners, but should be conceptualised as discourse markers. The results exhibit interesting similarities and dissimilarities to the formal and functional patterns of EHM (אהמ) in Hebrew WhatsApp chats identified by Marmorstein (this collection). The final discussion compares these findings as to how formal variation is exploited in digital discourse.